Double Negative B Cell Is Associated With Renal Impairment in Systemic Lupus Erythematosus and Acts as a Marker for Nephritis Remission - You, Xujie; Zhang, Ruijun; Shao, Miao; He, Jing; Chen, Jiali; Liu, Jiajia; Zhang, Xia; Liu, Xu; Jia, Rulin; Sun, Xiaolin; Li, Zhanguo (Frontiers in Medicine, 2020)
Objective. Recent studies on double negative B cells (DN B cells) suggested their potential pathogenic roles in systemic lupus erythematosus (SLE). This study aimed to determine the circulating DN B cells in SLE patients and analyzed the clinical significance of the cell subset. Methods. Fifty-seven SLE patients and fifty healthy controls (HCs) were recruited in our study. Among the fifty-seven SLE patients, twenty-five had lupus nephritis (LN). All patients were followed up for 24 weeks. Peripheral B cell subsets were analyzed by flow cytometry. Results. DN B cells were significantly elevated in the SLE patients, especially in the patients with LN (p<0.01). DN B cells showed a positive correlation with 24-hour urine protein excretion (24h-UPE) levels (r=0.444, p=0.034) in LN patients. DN B cells were inversely correlated with evaluated glomerular filtration rate (eGFR) (r=-0.351, p=0.011). DN B cells had a positive correlation with plasma cells (r=0.484, p<0.001) and memory B cells (r=0.703, p<0.001). After treatment, decreased DN B cells were associated with LN alleviation (p=0.002). In the follow-up, the remission rate of LN patients with decreased DN B cells was significantly higher than LN patients with increased DN B cells (83.33% versus 25.00%, p=0.030) at week 24. Conclusions. This study suggests that the peripheral DN B cells are positively correlated with the severity of renal damage in LN patients and this subset may be used as a prognostic marker in LN.